A survey on internet of things architecture, protocols, possible applications, security, privacy, real-world implementation and future trends - Kraijak, Surapon; Tuwanut, Panwit (My University, 2016)
The Internet is dramatically evolving and creating various connectivity methodologies. The Internet of Things (IoT) is one of those methodologies which transforms current Internet communication to Machine-to-Machine (M2M) basis. Hence, IoT can seamlessly connect the real world and cyberspace via physical objects that embed with various types of intelligent sensors. A large number of Internet-connected machines will generate and exchange an enormous amount of data that make daily life more convenient, help making a tough decision and provide beneficial services. This paper not only describes about the evolution and how important of IoT in daily life, the generic architecture, its most widely used protocols, numerous possible applications but also concern over security and privacy issues in IoT, real-world implementation of IoT system by using Arduino and its future trends. The IoT probably becomes one of the most popular networking concepts that has the potential to bring out many benefits.
Keywords: Architecture; Internet of Things; IoT Application; IoT Implementation; Privacy; Protocols; Security